Polyvinyl alcohol sponge for embolotherapy: particle size and morphology. - Jack, C R; Forbes, G; Dewanjee, M K; Brown, M L; Earnest, F (American Journal of Neuroradiology, 1985)
The size and morphology of particulate polyvinyl alcohol (PVA) sponge prepared by a blender technique for embolotherapy were analyzed by light and scanning electron microscopy. Techniques for preparation and sizing of PVA sponge particles are described. Two types of particulate material, differing in both size and morphology, were found. Large particles (greater than 50 micron) had irregular shapes and sharp, jagged edges. Smaller particles (2-50 micron) were more numerous. Attempts to characterize the smaller particles were unsuccessful. Preparation of PVA sponge particles using the blender technique is a viable choice in external carotid neuroembolization procedures. However, the potential effects of small particles possibly causing cranial nerve palsies does need consideration.